The representation of HIV/AIDS and hepatitis B in the dentistry context - Wakayama, Bruno [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Garbin, Artênio Jose Saliba; Junior, Orlando Adas Saliba; Garbin, Artênio Jose Isper [UNESP] (Journal of Infection in Developing Countries, 2021)
Introduction: HIV/AIDS and hepatitis B are diseases with major epidemiological and social impacts, with important effects in the dentistry context. This study aimed to compare the knowledge, presence, and manifestation of discriminatory and stigmatizing acts of dental surgeons, dental assistants, and dental students concerning social representations of HIV/AIDS and hepatitis B. Methodology: This cross-sectional, quantitative study was carried out in Brazil with primary health care dental surgeons (n = 219) and dental assistants (n = 152) in 40 municipalities and dental students of a public university (n = 179). The z-test for proportions (p ≤ 0.05) was used for data analysis to compare the three groups. Results: We found statistically significant differences regarding knowledge about HIV/AIDS and hepatitis B, with a higher percentage of correct answers by dental surgeons (97.7%). Regarding infection, the fear of contracting HIV/AIDS was more representative, whereas hepatitis B was more mentioned concerning the risk of infection. In general, only 30.7% and 42.2% of individuals would accept care from professionals with HIV/AIDS and hepatitis B, respectively; assistants and students had the higher proportion of refusal of care. Also, a higher proportion of assistants (47.4%) believed there are different conducts in the care of patients with HIV and hepatitis B. Conclusions: The knowledge of individuals about infectious diseases is still inconsistent, especially among dental assistants and students. Moreover, these groups showed a silent and hidden presence and manifestation of discriminatory and stigmatizing attitudes, with greater representativeness for HIV/AIDS.
Keywords: Dentistry; Hepatitis B; HIV